2009
DOI: 10.1111/j.1754-4505.2008.00068.x
|View full text |Cite
|
Sign up to set email alerts
|

Toothache pain: Behavioral impact and self‐care strategies

Abstract: A computer‐assisted telephone interview in Maryland of adults who had low income and were Hispanic, Black, and White and who had experienced a toothache during the previous 12 months was conducted. Respondents reported a high prevalence of toothaches, with 44.3% having experienced more than five toothaches during the preceding 10 years. Pain intensity associated with the most recent toothache was high with 45.1% of the respondents reporting the highest pain possible. Pain interfered with many aspects of normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
62
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 40 publications
5
62
0
8
Order By: Relevance
“…These behaviors could be interpreted by the nature of pain they suffer, financial factors allowing them to visit the dentist some but not all the time, or the efficacy of the remedy they use. This conforms to other researches which found that toothache sufferers used combination of self-care and formal care strategies with nonprescription medicines and self-care remedies being used as a temporary solution usually preceding dental clinic visits [14,15,16,17]. Statistically, the results revealed that majority of the participants 48.7% were between third to fifth decade.…”
Section: Discussionsupporting
confidence: 70%
“…These behaviors could be interpreted by the nature of pain they suffer, financial factors allowing them to visit the dentist some but not all the time, or the efficacy of the remedy they use. This conforms to other researches which found that toothache sufferers used combination of self-care and formal care strategies with nonprescription medicines and self-care remedies being used as a temporary solution usually preceding dental clinic visits [14,15,16,17]. Statistically, the results revealed that majority of the participants 48.7% were between third to fifth decade.…”
Section: Discussionsupporting
confidence: 70%
“…People will often use prescription and non-prescription medications as well as home remedies to self-manage the pain of a toothache (Gilbert et al, 2000). In fact, most low-income patients will utilize a self-care method before attempting to visit a dentist (Riley et al, 2004;Cohen et al, 2009). In our study, we found similar frequencies of users reporting going to the dentist (44% of Actions reported) or taking medication (43% of Actions reported) as a result of their toothache, suggesting a high rate of utilization of self-management strategies.…”
Section: Discussionmentioning
confidence: 99%
“…It is of great interest that the impacts on daily living and common actions taken to manage toothache-associated pain we observed in Twitter users are similar to previous reports using other methods. For example, a telephone survey study found that the most frequently reported behavioral effects of toothache are mood changes, difficulty eating, worry, and disruptions in sleep (Cohen et al, 2009). Although we did not attempt to infer mood from tweets, we did find that most users expressed various levels of distress in response to a toothache, as in the following example: "This toothache is preventin [sic] me from my happiness :(".…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many orofacial pain conditions have overlapping presentations, and diagnostic uncertainty is frequently encountered in clinical practice. 5 Dental pain may cause difficulty in eating, socialization and sleep, thus diminishing work productivity and influencing the need for dental care 6,7 Oro-facial problems are highly prevalent among both children and adults, although they are seldom life-threatening, many are chronic. Typically they have acute stages that are treatable and of short duration.…”
Section: Introduction:-mentioning
confidence: 99%